From Craft to Science: Embedding Physics of Materials into Product-Based Learning in Cosmetology Education - Astrid Sitompul; Asrah Rezki Fauzani; Habibah Hanim Lubis; Vita Pujawanti Dhana; Irmiah Nurul Rangkuti; Siti Wahidah; Hendro Sudartono; Erni Erni; Murni Astuti (Postgraduate, University of Mataram, 2025)
Fantasy hair styling in vocational cosmetology is commonly treated as a tacit craft activity, leaving limited evidence that material and geometry choices lead to ergonomic and stable designs. This study aimed to develop and validate craft-based support frames for fantasy buns while making materials-science and basic biomechanics concepts explicit. Using a 4D Research and Development model (Define–Design–Develop–Disseminate), undergraduate cosmetology students produced three frame variants (foam, thin wire, and polymer mesh). Product quality was evaluated by three cosmetology/beauty-education experts using a 1–5 Likert rubric covering aesthetics (neatness, proportion, creativity, harmony) and ergonomics (comfort, lightweight, ease of application/removal, positional stability). Three models conducted short wear-and-movement trials (standing, walking, head turns). Quantitative scores were converted to percentages and categorized; expert comments were analyzed thematically. Aesthetic performance averaged 87% (Very Good: neatness 90%, proportion 85%, creativity 88%, harmony 85%). Ergonomic performance averaged 83% (Very Good: comfort 85%, lightweight 82%, ease 80% [Good], stability 85%), with frame weights ranging from 500 to 2,000 g. These results indicate that craft-based frames can produce visually coherent and ergonomically acceptable fantasy buns while supporting concept-based reasoning; future work should strengthen durability and application techniques and extend trials to longer wear durations.